Copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel, preparation method thereof and application of copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel in detection and elimination of lead ions

Through the combination of copper-doped zinc sulfide quantum dots and sodium alginate composite fluorescent gel, the problem of difficult coupling of lead ion detection and removal in the prior art is solved, and the rapid, accurate detection and efficient removal of lead ions are achieved. Suitable for food quality control.

CN119120011APending Publication Date: 2024-12-13SOUTH CENTRAL UNIVERSITY FOR NATIONALITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411218263.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing lead ion detection methods and removal methods are difficult to couple, and the energy transfer between the nano-effect fluorescence probe and the quantum dot leads to fluorescence quenching, affecting the detection results, and the composite adsorbent material has a great impact on the sensitivity of fluorescence detection, which cannot be Effectively control lead ion contamination.

Method used

A composite fluorescent gel is used to combine copper-doped zinc sulfide quantum dots and sodium alginate, and a composite fluorescent gel is formed by heating and sonication. Combined with nano-effect fluorescent probes and sodium alginate, the accurate detection and synchronous removal of lead ions are achieved.

Benefits of technology

It realizes rapid, accurate detection and efficient removal of lead ions, low cost and convenient operation, and is suitable for quality control of foods such as liquor and tea, and overcomes the biotoxicity and secondary pollution problems of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005022200890000061
    Figure BDA0005022200890000061
  • Figure BDA0005022200890000071
    Figure BDA0005022200890000071
  • Figure HDA0005022200900000011
    Figure HDA0005022200900000011
Patent Text Reader

Abstract

A preparation method of the copper-doped zinc sulfide quantum dot-sodium alginate composite gel comprises the following steps: sequentially adding a copper source and a sulfur source into a zinc source solution, and adjusting the pH value; stirring treatment is conducted under the protective atmosphere, heating reaction is conducted, and a copper-doped zinc sulfide quantum dot solution is obtained; mixing with acetone, centrifuging, washing, drying and dissolving in water to obtain a copper-doped zinc sulfide quantum dot solution; mixing the copper-doped zinc sulfide quantum dot with sodium alginate powder, heating, carrying out ultrasonic treatment, and standing at room temperature to obtain the copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel. The nano-effect fluorescent probe and the sodium alginate are effectively combined, the obtained composite fluorescent gel and the lead ions can generate a unique fluorescence quenching effect, the composite fluorescent gel is applied to the field of lead ion detection, accurate quantification of the content of the lead ions and synchronous and efficient removal of the lead ions can be achieved, and the composite fluorescent gel has the advantages of being high in accuracy, good in sensitivity, high in sensitivity and the like. The method has the advantages of low biotoxicity, environmental protection, low cost and the like and is suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical analysis and detection, and specifically relates to a copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel and a preparation method thereof, and application thereof in the field of detecting and eliminating lead ions. Background Art

[0002] Pb(II) is one of the heavy metal elements that seriously endangers human health and life safety. The maximum allowable residual amount and standard detection method of Pb(II) are usually strictly required and clearly stipulated. With the widespread use of lead in industrial production, it may remain excessively in beverages such as tea or liquor in the form of direct contact or indirect contamination. Therefore, the rapid detection and effective removal of Pb(II) in beverages is of great practical significance.

[0003] Quantitative detection is the first step to control Pb(II) pollution. Standard detection methods for lead ions usually include cold atomic absorption spectroscopy (CV-AAS), inductively coupled plasma mass spectrometry (ICP-MS) and atomic fluorescence spectroscopy (AFS), but the detection costs involved are high, the detection time is long, the operation is complicated and requires professionals, which is not conducive to promotion. Fluorescence sensing based on nanomaterials has also become a research hotspot due to its high sensitivity to lead ions, good specificity and real-time monitoring advantages. However, existing methods usually only perform quantitative detection and cannot effectively control Pb(II) pollution. In addition, there are still major technical difficulties in combining fluorescence detection methods with removal methods. For example, the energy transfer between magnetic nanoparticles and quantum dots will cause fluorescence quenching and affect the detection results. At the same time, the composite adsorption material will have a certain impact on the sensitivity of fluorescence detection technology. Summary of the invention

[0004] The main purpose of the present invention is to effectively combine a nano-effect fluorescent probe with sodium alginate to form a new composite fluorescent gel to detect and distinguish lead ions, in order to solve the problems and shortcomings of the existing lead ion detection method and removal method, such as the difficulty in coupling. The new composite fluorescent gel has the advantages of high accuracy and good sensitivity for Pb(II), low biological toxicity, green environmental protection, low cost, etc., and can realize the precise quantitative detection and synchronous removal of Pb(II) in foods and beverages such as liquor, green tea, orange juice, etc., and is suitable for popularization and application.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a copper-doped zinc sulfide quantum dot-sodium alginate composite gel comprises the following steps:

[0007] (1) Synthesis of copper-doped zinc sulfide quantum dots (Cu:ZnS QDs):

[0008] The zinc source solution is mixed evenly, and a white precipitate is immediately generated after a copper source and a sulfur source are added in sequence, and then an alkali solution is added to adjust the pH value; the mixture is stirred under a protective atmosphere, and heated for reaction to obtain a clear and transparent copper-doped zinc sulfide quantum dot solution; the mixture is then mixed with acetone, centrifuged, washed, dried, and redissolved in water to obtain a copper-doped zinc sulfide quantum dot solution with bright yellow fluorescence;

[0009] (2) Preparation of hydrogel

[0010] The copper-doped zinc sulfide quantum dot solution is mixed with sodium alginate powder, subjected to heating and ultrasonic treatment, and allowed to stand at room temperature to obtain the copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel.

[0011] In the above scheme, the zinc source can be selected from one or more of zinc acetate, zinc nitrate, zinc chloride, etc.; the copper salt can be selected from one or more of copper sulfate, copper chloride, etc.

[0012] In the above scheme, the sulfur source can be selected from 3-mercaptopropionic acid.

[0013] In the above scheme, in step (1), the concentration of the zinc source solution is 20 to 25 mmol / L.

[0014] In the above scheme, the molar ratio of the copper source, the zinc source and the sulfur source is 1:12-12.5:20-25.

[0015] In the above scheme, alkaline solution is added in step (1) to adjust the pH value to 8.95-9.05.

[0016] Furthermore, the alkali solution can be a sodium hydroxide solution or the like, and its concentration is 0.8-1.1 mol / L.

[0017] In the above scheme, the stirring treatment time in step (1) is 15 to 30 minutes.

[0018] In the above scheme, the temperature of the heating reaction in step 1) is 160-170° C. and the time is 90-100 min.

[0019] In the above scheme, the obtained copper-doped zinc sulfide quantum dots are round in shape, with an average particle size of 8.0 to 8.5 nm; their strongest emission wavelength is 535 nm, showing bright yellow fluorescence.

[0020] In the above scheme, in the copper-doped zinc sulfide quantum dot dispersion in step (2), the concentration of copper-doped zinc sulfide quantum dots is 1 to 1.2 wt %.

[0021] In the above scheme, the mass ratio of the copper-doped zinc sulfide quantum dots introduced in step (2) to the sodium alginate powder is 1:1.5-2.5.

[0022] In the above scheme, the temperature used in the heating ultrasonic treatment step in step 2) is 60-70°C, the ultrasonic power is 450-500W, and the time is 30-40min.

[0023] In the above scheme, the standing time at room temperature is 8 to 12 hours.

[0024] The copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel prepared according to the above scheme, wherein the concentration of sodium alginate is 1.5-2.5wt%.

[0025] The copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel of the present invention can be used to quickly detect and remove lead ions in a lead-containing solution. The specific steps include: adding the copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel to a solution to be detected, reacting for a period of time, detecting the ratio (L0 / L) of the fluorescence brightness of the hydrogel beads (Cu:ZnS QDs-SA hydrogel beads) obtained before and after the reaction, and then establishing a linear relationship with the concentration of lead ions in the standard solution to achieve quantitative detection of lead ions in the solution to be detected.

[0026] Furthermore, the method for detecting the average fluorescence brightness before the reaction includes: adding copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel to a solution to be detected that does not contain lead ions, and after a period of reaction, detecting the fluorescence brightness L0 of the resulting hydrogel beads.

[0027] Furthermore, the method for detecting the average fluorescence brightness after the reaction includes: adding copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel to a solution to be detected with a known lead ion concentration, and after a period of reaction, detecting the fluorescence brightness L of the resulting hydrogel beads.

[0028] In the above scheme, the reaction time is more than 1 min.

[0029] Preferably, the reaction time is 1 to 3 minutes.

[0030] Preferably, the copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel is added to the solution to be detected in batches to obtain a higher lead ion removal rate.

[0031] In the above scheme, the volume ratio of the copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel to the solution to be tested is 1 to 1.5:10.

[0032] In the above scheme, the concentration of lead ions in the solution to be detected is 0 to 60 mg / kg.

[0033] Furthermore, the lead-containing solution is a beverage, including tea beverages (green tea, etc.), beverages (fruit juice drinks, etc.) or alcoholic beverages (white wine, etc.), etc.

[0034] The present invention also provides a method for rapid visual detection and simultaneous removal of lead ions using copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel, comprising the following steps:

[0035] 1) Add copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel to a sample solution free of lead ions. After 1 to 3 minutes, the gel solidifies to form spherical hydrogel beads. The formed hydrogel beads are taken out and their fluorescence intensity L0 is detected;

[0036] 2) A fixed volume (V) of copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel is dripped into the sample solution to be tested in batches. After 1 to 3 minutes, spherical hydrogel beads are solidified. At the same time, the lead ions of the metal gel quench the fluorescence of Cu:ZnS QDs in the gel solution. The formed hydrogel beads are taken out and the average fluorescence intensity L is detected;

[0037] 3) According to the ratio of the fluorescence brightness L0 / L and the linear relationship constructed above, the lead ion concentration in the sample solution is determined, and the lead ions are adsorbed and removed at the same time.

[0038] Furthermore, calcium lactate with a concentration of 0.5-2 wt % is added to the sample solution as an auxiliary curing agent.

[0039] Furthermore, in step 1), V is 5 to 10 mL.

[0040] Preferably, the copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel is added to the sample solution in 5 or more times (same amount each time).

[0041] Furthermore, the particle size of the spherical hydrogel beads formed by solidification in step 1) is 0.2 to 0.4 mm.

[0042] Furthermore, the concentration of lead ions in the sample solution is 0 to 60 mg / kg.

[0043] Furthermore, by adopting the above scheme of the present invention, the lead ions in the sample solution can be quantitatively determined through the linear relationship between the average fluorescence brightness ratio (L0 / L) of the Cu:ZnS QDs-SA hydrogel beads and the concentration of the standard solution (standard solution with known lead ion concentration); at the same time, the lead ions can be adsorbed and removed from the sample solution through the hydrogel beads.

[0044] The present invention provides for the first time a method for rapid visual detection and simultaneous removal of lead ions using a sodium alginate composite fluorescent hydrogel (copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel) coated with biocompatible quantum dots, which can achieve effective combination of nano-effect fluorescent probes and sodium alginate: the sodium alginate fluorescent hydrogel is added to a sample contaminated with lead ions, and the hydrogel is solidified into hydrogel beads with the assistance of calcium ions; in the above process, the lead ions will quench the fluorescent probes (copper-doped zinc sulfide quantum dots) in the hydrogel beads, and a linear relationship is established using the ratio of the average fluorescence brightness before and after quenching (L0 / L) and the concentration of the standard solution to achieve accurate quantification of the lead ions; at the same time, the hydrogel beads achieve adsorption and removal of lead ions through ion exchange, physical adsorption and other effects generated during the solidification of sodium alginate.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1) The detection-removal method based on the nano-effect fluorescent probe and sodium alginate gel of the present invention can realize the rapid and accurate detection of Pb(II), and can realize the synchronous and efficient removal of Pb(II).

[0047] 2) The fluorescence brightness of the obtained Cu:ZnS QDs-SA hydrogel beads gradually weakened with the increase of lead ion pollution concentration until it was completely quenched. The Cu:ZnS QDs-SA hydrogel beads can be used to simply and efficiently detect the lead ion content, effectively overcoming the shortcomings of traditional quantum dots (CdTe, CdSe, etc.) such as high biological toxicity and secondary pollution.

[0048] 3) The detection method involved in the present invention has low cost, convenient operation, rapidity, greenness and safety, does not require large-scale instruments, is particularly suitable for food quality control of liquor, tea, etc., and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The schematic diagram is a schematic diagram of the quantitative detection and simultaneous removal of Pb(II) according to the present invention.

[0050] Figure 2 This is a physical picture of the hydrogel dropping and hydrogel bead collection device used in an embodiment of the present invention.

[0051] Figure 3(A) is the transmission electron microscopy image of the Cu:ZnS QDs obtained in Example 1; (B) is the fluorescence spectrum of Cu:ZnS QDs before and after the reaction with Pb(II); (C) and (D) are the X-ray photoelectron spectrum and X-ray single crystal diffraction of Cu:ZnS QDs, respectively; (E) is the transmission electron microscopy image of Cu:ZnS QDs after reaction with Pb(II); (F) is the Fourier transform infrared spectrum of Cu:ZnS QDs before and after reaction with Pb(II); (G) is the Zeta potential diagram of Cu:ZnS QDs before and after reaction with Pb(II); (H) is the fluorescence lifetime diagram of Cu:ZnS QDs before and after reaction with Pb(II).

[0052] Figure 4 (A) is the Fourier transform infrared spectrum of the Cu:ZnS QDs-SA hydrogel spheres obtained in Example 1 before and after the adsorption of Pb(II); (B) is the Zeta potential diagram of the Cu:ZnS QDs-SA hydrogel spheres before and after the adsorption of Pb(II); (C) is the cold field scanning electron microscopy image of the Cu:ZnS QDs-SA hydrogel spheres; (D) is the cold field scanning electron microscopy image of the Cu:ZnS QDs-SA hydrogel spheres after reaction with Pb(II).

[0053] Figure 5 (A) is an optimized picture of the effect of sodium alginate and auxiliary curing agent calcium lactate concentration on gel beads; (B) and (D) are the fluorescence brightness curves and visual images of the time stability before and after the reaction with Pb(II); (C) is the optimized curve of the contact time between gel beads and Pb(II) during device operation.

[0054] Figure 6 (A) is the quenching effect of Pb(II) at a concentration of 0-60 mg / kg on the fluorescence brightness of Cu:ZnS QDs-SA hydrogel beads; (B) is the linear fitting curve between the fluorescence brightness ratio (L0 / L) of the hydrogel beads and the Pb(II) concentration; (C) is a comparison of the results of the hydrogel beads and the detection results by the standard atomic absorption method; (D) is a picture of the adsorption effect of the hydrogel on the Pb(II) residue in green tea beverage after the device cycle when the initial concentration is 45 mg / kg. DETAILED DESCRIPTION

[0055] The applicant will further explain the present invention in detail below in conjunction with specific embodiments so that those skilled in the art can more clearly understand the present invention. However, the following content should not be construed as limiting the scope of protection of the claims of the present invention.

[0056] The chemical reagents and solvents used in the examples are all analytically pure. The stirring is carried out using a magnetic stirrer.

[0057] Example 1

[0058] A copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel, the preparation method of which comprises the following steps:

[0059] (1) Synthesis of Cu:ZnS quantum dots:

[0060] 4.8mmol zinc acetate dihydrate was dissolved in 200mL ultrapure water, and ultrasonicated until completely dissolved. 1mL of 0.4mol / L copper sulfate pentahydrate solution and 8-10mmol of 3-mercaptopropionic acid were added in sequence under stirring at 500rpm, and a milky white precipitate was immediately generated. Sodium hydroxide solution (concentration of 1mol / L) was added dropwise to adjust the pH to 9; then stirred for 30min under nitrogen protection, and then transferred to a polytetrafluoroethylene reactor and placed in a high-temperature oven at 170°C for reaction for 100min to obtain a clear and transparent Cu:ZnS QDs solution; then it was quickly mixed with acetone at 1:2 (v:v), centrifuged at 9000r / min for 10min, and a white quantum dot precipitate was obtained; the obtained precipitate was washed three times with acetone, dried and redissolved in water, and stored at 0-4°C to obtain a Cu:ZnS quantum dot solution (Cu:ZnS QDs solution) with bright yellow fluorescence under 365nm ultraviolet light;

[0061] (2) Preparation of Quantum Dots-Sodium Alginate Fluorescent Hydrogel (Cu:ZnS QDs-SA Hydrogel):

[0062] Accurately weigh 1 g of sodium alginate powder and mix it with 50 mL of the Cu:ZnS QDs solution (the concentration of copper-doped zinc sulfide quantum dots is 1.2 wt%) obtained in step (1); ultrasonically treat at 70°C for 30 min (power is 500 W) to ensure that there are no lumps, and let it stand at room temperature for 12 h; prepare a copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent hydrogel (Cu:ZnS QDs-SA hydrogel solution; a uniform viscous liquid with bright yellow fluorescence) with a sodium alginate concentration of 2 wt%.

[0063] After testing, the copper-doped zinc sulfide quantum dots obtained by the present invention have good solubility in methanol and ethanol, and no white precipitate can be obtained; n-propanol, isopropanol, cyclohexanone and the quantum dot solution are separated and the quantum dots cannot be precipitated; benzene and DMF will affect the fluorescence intensity of the quantum dots and cannot precipitate the quantum dots with a high yield; only acetone used in step (1) can efficiently precipitate the quantum dots and complete the subsequent purification without affecting the performance of the quantum dots.

[0064] Application Examples

[0065] The copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent hydrogel obtained in Example 1 is applied to rapid visual detection and simultaneous removal of lead ions, and the specific steps include:

[0066] 1) Adoption Figure 2 The hydrogel dropping and hydrogel bead collecting device;

[0067] Insert a hose connected to a peristaltic pump below the Cu:ZnS QDs-SA hydrogel solution, slightly magnetically stir the sample solution to be tested, and then adjust the flat coarse mesh filter connected to the reciprocating push rod to below the liquid surface, wherein the sample solution to be tested consists of 5 mL of a lead stock solution with a known lead ion concentration (concentration of 0-600 mg / kg), 5 mL of a calcium lactate solution (concentration of 1 wt%), and 40 mL of ultrapure water;

[0068] 2) Visual detection and simultaneous removal of lead ions by Cu:ZnS QDs-SA hydrogel;

[0069] ① The gel sol of fixed volume V (5 mL each time) was automatically delivered to the top of the connecting tube by a peristaltic pump in 5 times, and the viscous gel solution was automatically dripped into the sample solution to be tested without lead ions (lead ion concentration was 0 mg / kg). After 3 minutes, the dripped hydrogel solution solidified into spherical Cu:ZnS-SA hydrogel beads. At the same time, the lead ions of the metal gel quenched the fluorescence of Cu:ZnS QDs in the gel solution.

[0070] Subsequently, the formed Cu:ZnS-SA hydrogel beads in the sample solution were collected by a coarse mesh filter connected to a reciprocating push rod, and were pulled out of the liquid surface and rolled down the inclined coarse mesh filter into the collection cup;

[0071] The collected Cu:ZnS-SA hydrogel beads were placed on a black non-fluorescent acrylic base plate, quickly transferred to a UV dark box, and photographed with a smart camera under 365nm UV light with the same parameters, and the image results were recorded and analyzed to obtain the average fluorescence intensity L0 of the hydrogel beads;

[0072] ② Using the above test method, the lead ion content in a series of lead ion standard solutions with different concentrations (lead ion concentration is 0.1-60 mg / kg) was detected using Cu:ZnS QDs-SA hydrogel beads, and the average fluorescence brightness data L of the hydrogel beads falling into the collection cup after each drop was collected; the average fluorescence brightness ratio of the hydrogel beads (L0 / L) extracted by the software was used as the ordinate, and the corresponding lead ion concentration C was used as the abscissa to establish a corresponding standard curve; quantitative detection of lead ions was achieved.

[0073] By adopting the above method of the present invention, when the Cu:ZnS QDs-SA hydrogel contacts the lead ions in the standard solution, the lead ions are adsorbed and removed by physical adsorption and ion exchange; after multiple gel adsorptions by the automatic device, the concentration of lead ions in the sample solution is continuously reduced, and the lead ion concentration in the sample solution is tested by the flame atomic absorption standard method to calculate the clearance rate; at the same time, the real-time concentration of lead ions can be monitored during the cycle. The concentration of lead ions is continuously reduced after each hydrogel drop process, and the residual lead ions can be accurately determined by the hydrogel beads.

[0074] The above method was used to test and recover Pb(II) in real samples. The results are shown in Table 1.

[0075] Table 1 Detection and recovery results of Pb(II) in real samples

[0076]

[0077]

[0078] Figure 3 (A) is a transmission electron microscopy image of the Cu:ZnS QDs obtained in Example 1, from which it can be seen that the quantum dots are uniformly dispersed spherical particles with an average particle size of 8.18 nm; (B) is a fluorescence spectrum of Cu:ZnS QDs before and after the reaction with Pb(II), and the fluorescence of the quantum dots is significantly quenched after the reaction with Pb(II); (C) and (D) are X-ray photoelectron energy spectrum and X-ray single crystal diffraction images of Cu:ZnS QDs, respectively, reflecting the elemental composition and crystal structure of the quantum dots, indicating the successful synthesis of the quantum dots; (E) is a transmission electron microscopy image of Cu:ZnS QDs after the reaction with Pb(II), and the quantum dot particles in the image become highly aggregated compared to Figure A, indicating the fluorescence quenching effect caused by the aggregation of quantum dots induced by Pb(II); (F) is a transmission electron microscopy image of Cu:ZnS QDs before and after the reaction with Pb(II). The Fourier transform infrared spectrum of QDs shows that there is no bond between Pb(II) and quantum dots and their surface modification groups, indicating that the aggregation quenching is caused by charge change; (G) is the Zeta potential diagram of Cu:ZnS QDs before and after the reaction with Pb(II). After the reaction with Pb(II), the surface charge of the quantum dots is neutralized, so that the electrostatic repulsion is reduced and the quantum dots aggregate; (H) is the fluorescence lifetime diagram of Cu:ZnS QDs before and after the reaction with Pb(II). It can be seen that the Cu:ZnS QDs obtained by the present invention will produce rapid fluorescence quenching after the action of lead ions.

[0079] Figure 4(A) is the Fourier transform infrared spectrum of the Cu:ZnS QDs-SA hydrogel ball obtained in Example 1 before and after the adsorption of Pb(II), which shows that the adsorption site of sodium alginate for Pb(II) is on -OH; (B) is the Zeta potential diagram of the Cu:ZnS QDs-SA hydrogel ball before and after the adsorption of Pb(II), and the obvious change of Zeta potential indicates that there may be ion exchange; (C) is the cold field scanning electron microscopy image of the Cu:ZnS QDs-SA hydrogel ball, which can clearly see that the hydrogel ball has a loose and porous structure; (D) is the cold field scanning electron microscopy image of the Cu:ZnS QDs-SA hydrogel ball after the reaction with Pb(II), and the loose and porous structure is significantly reduced. The comparison before and after proves that the Cu:ZnS QDs-SA hydrogel ball has a certain physical adsorption effect on Pb(II).

[0080] Figure 5 (A) is an optimization diagram of the effect of the concentration of sodium alginate and auxiliary curing agent calcium lactate on the gel beads. It can be seen that on the basis of a fixed volume, the preferred concentrations of sodium alginate and calcium lactate are 2wt% and 1wt%, respectively; (B) and (D) are the fluorescence brightness curves and visual images of the time stability before and after the reaction with Pb(II); (C) is the optimization curve of the contact time between the gel beads and Pb(II) during the operation of the device. The above results show that the reaction time is 1-3 minutes and the image acquisition is completed within 5 minutes.

[0081] Figure 6 (A) shows the quenching effect of Pb(II) at concentrations of 0-60 mg / kg on the fluorescence brightness of Cu:ZnS QDs-SA hydrogel beads. When the Pb(II) concentration continues to increase, the visual fluorescence of the quantum dots is significantly quenched. (B) shows the linear fitting curve between the fluorescence brightness ratio (L0 / L) of the hydrogel beads and the Pb(II) concentration. The linear equation is Y=0.00301X+1.0045, R 2 =0.9932; (C) is a comparison between the results of the gel beads and those detected by the standard atomic absorption method. After verification by the standard method, it is shown that the accuracy of the method described in the present invention is better; (D) is a picture of the adsorption effect of the hydrogel on the Pb(II) residue in green tea beverage after repeated removal by the device when the initial concentration is 45 mg / kg. After multiple adsorptions, efficient removal of Pb(II) can be achieved.

[0082] Comparative Example 1

[0083] A copper-doped zinc sulfide quantum dot, the preparation method of which comprises the following steps:

[0084] 2mmol zinc chloride and 0.04mmol copper sulfate pentahydrate were dissolved in 200mL ultrapure water, ultrasonicated until completely dissolved, stirred at 500rpm under nitrogen protection for 15-30min, and then 5mL of 3.2mmol / L 3-mercaptopropionic acid solution was added. After stirring for 10min, 10mL of 0.5mol / L Na2S solution was quickly injected. The resulting mixed solution was exposed to air and aged at 60°C for 8h to obtain a copper-doped zinc sulfide quantum dot solution.

[0085] After testing, the fluorescence performance of the copper-doped zinc sulfide quantum dots obtained in this comparative example is weak, and the fluorescence emission is not bright under 365nm ultraviolet light; it has no response to lead ions and cannot be used to achieve fluorescent visual detection of lead ions.

[0086] Comparative Example 2

[0087] A manganese-doped zinc sulfide quantum dot, the preparation method of which comprises the following steps:

[0088] 0.95mmol zinc nitrate and 0.05mmol manganese acetate were dissolved in 15mL ultrapure water (the total amount of zinc nitrate and manganese acetate was 1mmol), and then 3mmol thiourea was added to the mixed solution and stirred for another 1h after stirring at 500rpm; the mixture was transferred into a polytetrafluoroethylene reactor and placed in a high-temperature oven at 180°C for 15h to obtain orange-red emitting manganese-doped zinc sulfide quantum dots.

[0089] After testing, the obtained manganese-doped zinc sulfide quantum dots have poor water solubility, no surface hydrophilic ligands, and the quantum dots exist in the solution in a suspended state, making it difficult to compound with sodium alginate to form a fluorescent gel; in addition, the obtained quantum dots have no response to lead ions, and when the quantum dots are mixed with a higher concentration of lead ions for reaction, no fluorescence quenching phenomenon similar to that of the present invention occurs.

[0090] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A method for preparing copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel, characterized in that: The steps include: (1) Synthesis of copper-doped zinc sulfide quantum dots: A copper source and a sulfur source are sequentially added to a zinc source solution, and then an alkali solution is added to adjust the pH value; the solution is stirred and heated under a protective atmosphere to obtain a clear and transparent copper-doped zinc sulfide quantum dot solution; the solution is then mixed with acetone, centrifuged, washed, dried and dissolved in water to obtain a copper-doped zinc sulfide quantum dot solution with bright yellow fluorescence; (2) Preparation of hydrogel The copper-doped zinc sulfide quantum dot solution is mixed with sodium alginate powder, subjected to heating and ultrasonic treatment, and allowed to stand at room temperature to obtain the copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel.

2. The preparation method according to claim 1, characterized in that: The zinc source is one or more of zinc acetate, zinc nitrate and zinc chloride; the copper salt is one or more of copper sulfate and copper chloride; and the sulfur source is 3-mercaptopropionic acid.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the copper source, the zinc source and the sulfur source is 1:12-12.5:20-25.

4. The preparation method according to claim 1, characterized in that: In step (1), the pH value is adjusted to 8.95-9.

05.

5. The preparation method according to claim 1, characterized in that: The heating reaction in the step adopts a temperature of 160-170° C. and a time of 90-100 min.

6. The preparation method according to claim 1, characterized in that: In the copper-doped zinc sulfide quantum dot dispersion in step (2), the concentration of copper-doped zinc sulfide quantum dots is 1 to 1.2 wt %.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the copper-doped zinc sulfide quantum dots to the sodium alginate powder introduced in step (2) is 1:1.5-2.

5.

8. The preparation method according to claim 1, characterized in that: The temperature used in the heating ultrasonic treatment step in step (2) is 60-70° C., the ultrasonic power is 450-500 W, and the time is 30-40 min.

9. The copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel prepared by the preparation method according to any one of claims 1 to 8.

10. The use of the copper-doped zinc sulfide quantum dot-sodium alginate composite fluorescent gel according to claim 9 in detecting and removing lead ions in a lead-containing solution, characterized in that: The specific steps include: adding copper-doped zinc sulfide quantum dots-sodium alginate composite fluorescent gel to the solution to be detected, reacting for a period of time, detecting the ratio of fluorescence brightness before and after the reaction, L0 / L, and then establishing a linear relationship with the concentration of lead ions in the standard solution to achieve quantitative detection of lead ions in the solution to be detected.